(untitled) (Canadian Journal of Counselling and Psychotherapy, 2012)
Professional ethical guidelines commonly advise counsellors to avoid dual relationships wherever possible but generally have not provided guidance for situations where this is not feasible. This leaves queer, Two Spirit, and/or trans counsellors open to negative judgements, possible accusations of unprofessionalism, and practices of self-surveillance that limit their ability to live, work, and actively participate in the communities they serve. We argue that prohibiting dual relationships will neither end client exploitation nor account for the benefits that properly managed dual relationships can offer. The term multiple relationships may better reflect the complexity of relationships in queer, Two Spirit, and/or trans communities and acknowledges that they contain the potential of both harms and benefits for clients. We advocate for a richer engagement with ethics as a living entity that requires that we respond collectively as helping professions to ensure the care of marginalized communities without putting the burden of care on the backs of community members. We propose guidelines that call for the inclusion of all parties (counsellors, clients, and supervisors), transparency, full disclosure, and development of a plan and rationale for counsellors’ responsibilities in all encounters with clients both within and outside the clinical setting.